COVID-19 and European Industry: Global Shocks, Local Shocks and Value-Chain Restructuring - John Humphrey; Grzegorz Lechowski (WZB Berlin Social Science Center, 2020)
How the complex value-chain structures in European manufacturing sectors will absorb the wave of economic disruption.
Keywords: 300; contagious disease; Coronavirus; COVID-19; economic impact; epidemic; Europe; industry; value added; value chain